Case Report on Intravenous Ranitidine Induced Anaphylactic Reaction in Cholangiocarcinoma Patient - Moudgil, Khayati; Ponnusankar, Sivasankaran (Indian Journal of Pharmacy Practice)
Ranitidine hydrochloride being one of the most commonly used drugs and its use is well provident. Furthermore, anaphylactic reactions are rarely observed with the use of ranitidine hydrochloride. Hypersensitivity reactions are usually common in clinical practice but adverse reaction to intravenous ranitidine is very rare. Here we report a case, where the patient developed an anaphylactic reaction with a single dose of intravenous ranitidine in cholangiocarcinoma patient. This report highlights the importance of recognition of the serious adverse events that might follow and the need for cautiousness with the use of ranitidine in the future prospects.
Keywords: Adverse drug reaction; Flare; Histamine; Ranitidine; Itching; Wheal